IMPLEMENTASI PENGELOLAAN FILANTROPI ISLAM DI MADRASAH IBTIDAIYAH MA’ARIF NU 1 LANGGONGSARI - Fina Latifatunnida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Islamic philanthropy is an essential instrument in strengthening socio-religious values within educational institutions, including madrasahs at the basic level. This study aims to describe the implementation, supporting factors, and inhibiting factors of Islamic philanthropy management at MI Ma’arif NU 1 Langgongsari. Employing a qualitative descriptive method, data were collected through interviews, observations, and document analysis involving school leaders, teachers, school committee members, and program coordinators. The findings reveal that philanthropic activities are carried out through structured programs such as weekly infaq collection, zakat fitrah management, and class-based social assistance initiatives. The primary supporting factors include a strong religious culture, institutional commitment, and community involvement, whereas inhibiting factors consist of limited digital reporting systems, uneven student participation, and the absence of formal written standard operating procedures. This study demonstrates that well-managed philanthropic practices contribute significantly to students’ character development and strengthen the school's social solidarity ecosystem. The implications highlight the need for governance refinement and digitalization to enhance transparency and sustainability in school-based Islamic philanthropy